Three‐dimensional organic–inorganic hybrid sodium halide perovskite: C4H12N2·NaI3 and a hydrogen‐bonded supramolecular three‐dimensional network in 3C4H12N2·NaI4·3I·H2O. Issue 6 (23rd May 2018) - Chen, Xiao-Gang; Gao, Ji-Xing; Hua, Xiu-Ni; Liao, Wei-Qiang
Abstract : Two new organic–inorganic hybrid sodium halides based on the piperazinediium dication have been synthesized, with C4 H12 N2 ·NaI3 presenting a three‐dimensional perovskite structure and 3C4 H12 N2 ·NaI4 ·3I·H2 O showing a three‐dimensional hydrogen‐bonded supramolecular network. Abstract : The rational selection of ligands is vitally important in the construction of new organic–inorganic hybrid three‐dimensional perovskite complexes. As part of an exploration of perovskite‐type materials, two new Na–I compounds based on the piperazine ligand, namely poly[piperazinediium [tri‐μ‐iodido‐sodium]], {(C4 H12 N2 )[NaI3 ]} n, 1, and catena ‐poly[tris(piperazinediium) [[triiodidosodium]‐μ‐iodido] triiodide monohydrate], {(C4 H12 N2 )3 [NaI4 ]I3 ·H2 O} n, 2, have been synthesized by adjusting the stoichiometric ratio of sodium iodide and piperazine, and were characterized by single‐crystal X‐ray diffraction. In the crystal structures of1 and2, each Na I cation is linked to six I atoms, but the compounds show completely different configurations. In1, the structure includes a perovskite‐like array of vertex‐sharing NaI6 octahedra stretching along the direction of the three axes, and each piperazinediium dication is enclosed in the NaI3 perovskite cage. However, in2, each Na I atom bridges a single I atom to form a one‐dimensional linear chain, and complex intermolecular hydrogen bonds connect these one‐dimensional chains into a three‐dimensional supramolecular network.